Promotion of Service Delivery in Terms of the Social Contract Theory in South Africa's Legal Framework - Ebi Okeng; Anthony Chima Diala (Potchefstroom Electronic Law Journal)
As is evident in the prevailing water and electricity rationing, South Africa is reeling from a crisis of poor service delivery. Against the background of its apartheid history and liberal constitution, this article examines how South Africa's legal framework promotes efficient service delivery in the context of a social contract theory. Using a literature review and content analysis of legislation, this article argues that basic service delivery is a human right that underlies the core function of the State regarding its social contract with citizens. The article critiques cooperative governance and the demarcation of service delivery duties between the spheres of government in the 1996 Constitution, the Municipal Structures Act, the Municipal Systems Act, and the Traditional Leadership and Governance Framework Act. It demonstrates how the legal framework places a heavy burden on the local government to provide basic amenities. By highlighting how a social contract informs the purpose of the constitutional State, the article demonstrates why service delivery must be taken seriously in a nation desperately in need of socio-economic transformation.